2013
DOI: 10.4244/eijv9i3a55
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparison of everolimus-eluting and biolimus-eluting stents

Abstract: This first clinical study failed to demonstrate any significant difference regarding safety or efficacy between these two types and generations of drug-eluting stents (DES).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(9 reference statements)
0
7
1
Order By: Relevance
“…26 Recently, Puricel et al reported that at 2 years the frequency of stent thrombosis after BES implantation is equal to that after EES implantation. 27 According to the Japanese Circulation Society guidelines, DAPT should be taken for at least 1 year. 28 However, recent data have revealed that the incidence of stent thrombosis at 24 months was not different between 6-month and 24-month DAPT groups after second-generation DES implantation.…”
Section: Possibility For Shortening the Duration Of Daptmentioning
confidence: 99%
“…26 Recently, Puricel et al reported that at 2 years the frequency of stent thrombosis after BES implantation is equal to that after EES implantation. 27 According to the Japanese Circulation Society guidelines, DAPT should be taken for at least 1 year. 28 However, recent data have revealed that the incidence of stent thrombosis at 24 months was not different between 6-month and 24-month DAPT groups after second-generation DES implantation.…”
Section: Possibility For Shortening the Duration Of Daptmentioning
confidence: 99%
“…After the establishment of BP-BES's noninferiority to DP-EES in randomized trials, 16,21,22 some recent studies have focused on evaluating the advantages of BP-BES over DP-EES. 11,12 Puricel and colleagues 12 compared clinical outcomes in 200 propensity-score-matched pairs of patients (one treated by EES and the other treated by BES) and reported that, at 24 months after PCI, MACE had occurred in 10.5% of the BP-BES group and in 11.5% of the DP-EES group, with no significant difference. At the one-year follow-up, an analysis of a single-center registry of unrestricted use of EES and Biomatrix BES in 406 propensity-score-matched pairs showed a similar rate of target-lesion failure, stent thrombosis, and patient-oriented composite outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Trials have shown the noninferiority of the biodegradable-polymer biolimus-eluting stent (BP-BES) to the previous generations of DESs; however, only a few investigators have compared the biodegradable-polymer with the durable-polymer DES in real-world registries. 11,12 Further analysis of large and comprehensive data registries seemed to be necessary to compare the efficacy and safety of those stents. During a 12-month follow-up period, we compared the incidence of major adverse cardiac events (MACE) in patients who underwent percutaneous coronary intervention (PCI) with the biodegradable-polymer biolimus-eluting stent (BP-BES) versus the incidence of MACE in patients who underwent PCI with the durable-polymer everolimus-eluting stent (DP-EES).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these excellent outcomes, it will be difficult to see any significant differences between BP-DES and EES. In a registry [48] including 814 patients with a median follow-up of 22 months, biolimus-eluting stents were similar to EES regarding safety (ST, MI or death) or efficacy (target vessel revascularization). In future clinical trials, more second-generation DES should be considered competitive comparators to corroborate the present finding.…”
Section: Possible Mechanisms Of Benefitmentioning
confidence: 99%